Violation of Article 15 of Law No. 5 Year 1999 against the Conditions for the Legality of a Contract in Article 1320 of the Civil Code (KUH Perdata) - Elsa, Elsa; Salim, Hartono Agus; Gymnastiar, Rigan; Tanaya, Velliana (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research aims to analyze the relationship between violations of Article 15 of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition and the requirements for the validity of contracts as stipulated in Article 1320 of the Civil Code (KUH Perdata). Article 15 of Law No. 5 Year 1999 prohibits business actors from abusing a dominant position in an agreement, including forcing other parties to agree to unfair or detrimental terms. This prohibition aims to maintain fair business competition and prevent monopolistic practices that may harm certain parties. In the context of Civil Law, violation of Article 15 of Law No. 5 of 1999 can affect the validity of the contract based on Article 1320 of the Civil Code, especially on the elements of agreement and lawful cause. This research uses a normative juridical research method, an approach that focuses on analyzing relevant laws and regulations, legal doctrines, and court decisions. This research also discusses the legal implications of such violations, including the possibility of canceling the contract (Batal Demi Hukum) by the court or the Business Competition Supervisory Commission (KPPU). By using a normative approach and case studies, this article provides insight into how the principle of freedom of contract must be balanced with compliance with the rules of fair business competition. This research is expected to contribute to the development of contract law and business competition in Indonesia.